2014
DOI: 10.1016/j.oooo.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer in young Jordanians: potential association with frequency of narghile smoking

Abstract: Narghile smoking is an independent risk factor associated with the development of oral cancer at a younger age. Prospective studies of its effect on the earlier development of oral cancer are needed to establish a cause-effect relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 34 publications
1
32
0
1
Order By: Relevance
“…The detrimental effects of cigarette smoking on oral and systemic health have been reported extensively 20–24 . Studies have reported that clinical and radiographic parameters of periodontal inflammation (such as probing depth [PD] ≥4 mm, clinical attachment loss [AL], and marginal bone loss [MBL]) are worse and numbers of missing teeth (MT) are higher among habitual cigarette smokers (CSs) than those who have never smoked 25–28 .…”
mentioning
confidence: 99%
“…The detrimental effects of cigarette smoking on oral and systemic health have been reported extensively 20–24 . Studies have reported that clinical and radiographic parameters of periodontal inflammation (such as probing depth [PD] ≥4 mm, clinical attachment loss [AL], and marginal bone loss [MBL]) are worse and numbers of missing teeth (MT) are higher among habitual cigarette smokers (CSs) than those who have never smoked 25–28 .…”
mentioning
confidence: 99%
“…The deleterious effects of tobacco smoking on oral and systemic health are well documented 11‐15 . Habitual tobacco smoking has also been associated with an increased expression of receptors of AGEs in the gingival tissues 16 .…”
mentioning
confidence: 99%
“…Further, an exploration of the Jordanian National Cancer Registry (620 cancer records) provided the information about 17% of water‐pipe smokers among cancer subjects. The conclusion was that water‐pipe smoking is an independent risk factor for development of oral cancer, mostly at a younger age . A similar study in Middle Eastern Populations including 50,000 cohort members provided information on the association of cancer mortality with cumulative lifetime water‐pipe use.…”
Section: Cancer Risks Associated With Smokingmentioning
confidence: 99%
“…Further, a relationship between the frequency of water‐pipe smoking and the age at oral cancer diagnosis has been reported. The more frequently patients used water‐pipe, the younger they were when diagnosed with oral cancer …”
Section: Toxicity Of Tobacco Smokementioning
confidence: 99%
See 1 more Smart Citation